Alterity, Alacrity, and Excess: Continental Philosophical Interpretations of the Figure of Abraham According to Franz Rosenzweig, Emmanuel Levinas, Jacques Derrida and Jean-Luc Marion - Miriam Feldmann Kaye (Religions, 2022)
I propose a new reading of a selection of continental philosophical interpretations of the nature of existentialism after the dialogical turn. This analysis will focus on the particular case study of the biblical character of Abraham as a case in point. Philosophical treatments thereof allow for a consideration of different but connected approaches through the study and re-readings of the character of Abraham, which begin with Kierkegaard’s well-known rendition of the sacrifice of Isaac. This study will focus on interpretations since Kierkegaard, with attention to the continental philosophical trend. The four thinkers I bring, all offered critiques, and even rejections of, a purely existential position. These positions are well-known in the field. However, Existentialism is never actually overcome despite these four critiques of Kierkegaard’s model of Abraham. I will demonstrate this through an analysis of the case of interpretations of the biblical figure of Abraham, showing the ways in which Kierkegaard remains present in dialogical philosophy and even deconstructionism. For Franz Rosenzweig, his stance is relational and thus is fascinated yet ambivalent towards the readiness of Abraham to sacrifice; Emmanuel Levinas admires Kierkegaard’s emphasis on the subject/ivity (Proper Names and Difficult Freedom); Jacques Derrida admires Abraham’s passion (Gift of Death and Abraham as Other); and for Jean-Luc Marion, Abraham’s sacrifice does not present a relinquishing of self, but rather, the phenomenological act symbolises returning a Gift.